The Impact of New Media on Shaping Public Opinion in the Post-Industrial Era. Government Regulations in the Fight Against Disinformation (Economic and Political Thought, 2019)
This article focuses on the process of spreading fake news on the Internet.Today, by means of the media, users are able to distribute and disseminatea range of alternative content. The article shows the changes and consequencesthat users of new media must face. As a result of the unprecedenteddevelopment of technology and disinformation that is spreading thereby,the tendency to fix erroneous beliefs in society is becoming more and morevisible. The Internet creates perfect conditions to give autonomous cellsan opportunity to quickly exchange information and confirm their beliefs.While traditional media are subject to institutional control, in the case ofsocial media communication possibilities seem unlimited as they are subjectonly to social control, which in turn translates into the amount of ripplingpernicious content.Dynamic development of technological solutions directly affects theplacement of disinformation in another dimension. Fake news has becomesuch an important problem in the media and social discourse that initiativeshave been taken in many countries to combat the spread of disinformationon the Web. The key element is, above all, building public awareness andidentifying false messages and sources that publish ‘fake news’.
Keywords: post-truth, fake news, information, disinformation, information society, social media